القيادة التحويلية وعلاقتها بالتغيير التنظيمي لدى أساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية - سوق اهراس - - صوالح محمد السعيد (My University, 2024)
ملخص الدراسة : الدراسة بعنوان القيادة التحويلية وعلاقتها بالتغيير التنظيمي لدى اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية لولاية سوق اهراس ، حيث هدفت إلى التأكد من وجود علاقة بين القيادة التحويلية والتغيير التنظيمي لدى اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية و طبقت الدراسة على عينة قوامها 30 أستاذا و أستاذة جامعية في معهد علوم وتقنيات النشاطات البدنية والرياضية بسوق اهراس ، حيث تم طرح التساؤل العام التالي: هل يوجد علاقة بين القيادة التحويلية والتغيير التنظيمي لدى اساتذة معهد علوم وقد وضعت بعض التساؤلات الجزئية تحت هذا التساؤل الرئيسي، و افترضت الدراسة الفرض العام التالي: يوجد علاقة بين القيادة التحويلية والتغيير التنظيمي لدى اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية سوق اهراس . واعتمدت الدراسة على المنهج الوصفي، أما فيما يخص أداة جمع البيانات فإنه قد تم الاستعانة بالاستبيان كأداة أساسية، و قد خلصت الدراسة إلى النتائج التالية: ومن اهم النتائج التي توصلت لها الدراسة انه هناك علاقة بين القيادة التحويلية والتغيير التنظيمي هناك خلاقة بين القيادة التحويلية والتغيير في الهيكل التنظيمي وفي التكنولوجيا وفي الموارد البشرية وانه هناك فروق ذات دلالة احصائية 0.05≥α حول القيادة التحويلية لمتغير السن والمستوى التعليمي ولسنوات الخبرة لدى اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية و استنتاج عام ان القيادة التحويلية نمط قيادي يحقق و يساعد على التعيير داخل المنظمات abstract : The study titled "Transformational Leadership and Its Relationship to Organizational Change among Faculty Members of the Institute of Physical Education and Sports Sciences in Souk Ahras Province" aimed to ascertain the relationship between transformational leadership and organizational change among faculty members of the Institute of Physical Education and Sports Sciences in Souk Ahras. The study included a sample of 30 university professors at the Institute, and it posed the general question: Is there a relationship between transformational leadership and organizational change among faculty members of the Institute of Physical Education and Sports Sciences in Souk Ahras The study assumed the general hypothesis that there is a relationship between transformational leadership and organizational change among faculty members of the Institute of Physical Education and Sports Sciences in Souk Ahras. It adopted a descriptive methodology, using a questionnaire as the primary data collection tool. The study concluded several results, notably that there is a relationship between transformational leadership and organizational change, specifically in organizational structure, technology, and human resources. Additionally, statistically significant differences (α≤ 0.05) were found in transformational leadership concerning variables such as age, educational level, and years of experience among faculty members. The general conclusion drawn was that transformational leadership is a leadership style that promotes and facilitates change within organization résumé : L'étude intitulée "Leadership transformationnel et sa relation avec le changement organisationnel chez les professeurs de l'Institut des Sciences et Techniques des Activités Physiques et Sportives de la wilaya de Souk Ahras" avait pour objectif de vérifier l'existence d'une relation entre le leadership transformationnel et le changement organisationnel chez les professeurs de l'Institut des Sciences et Techniques des Activités Physiques et Sportives. L'étude a été menée sur un échantillon de 30 professeurs et professeures de cet institut à Souk Ahras. La question générale posée était la suivante : Existe-t-il une relation entre le leadership transformationnel et le changement organisationnel chez les professeurs de l'Institut des Sciences et Techniques des Activités Physiques et Sportives ? Des questions partielles ont été formulées sous cette question principale, et l'étude a émis l'hypothèse générale suivante : Il existe une relation entre le leadership transformationnel et le changement organisationnel chez les professeurs de l'Institut des Sciences et Techniques des Activités Physiques et Sportives de Souk Ahras. L'étude a adopté la méthode descriptive. En ce qui concerne l'outil de collecte de données, le questionnaire a été utilisé comme outil principal. Les résultats de l'étude sont les suivants : L'une des conclusions les plus importantes de l'étude est qu'il existe une relation entre le leadership transformationnel et le changement organisationnel. Il existe une relation entre le leadership transformationnel et le changement dans la structure organisationnelle, la technologie et les ressources humaines. Il existe également des différences statistiquement significatives (α ≤ 0,05) concernant le leadership transformationnel selon l'âge, le niveau d'éducation et les années d'expérience des professeurs de l'Institut des Sciences et Techniques des Activités Physiques et Sportives. La conclusion générale est que le leadership transformationnel est un style de leadership qui favorise et aide au changement au sein des organisations
Keywords: القيادة; القيادة التحويلية; التغيير; التغيير التنظيمي; Leadership; ransformational Leadership; Organizational Change Change: Leadership; Leadership Transformationnel; Changement; Changement Organisationnel